The trip : Andy Warhol's plastic fantastic cross-country adventure - Davis, Deborah, 1952- (Atria Books, 2015)
"From the author of Strapless and Guest of Honor, a book about a little-known road trip Andy Warhol took from New York to LA in 1963, and how that journey - and the numerous artists and celebrities he encountered - profoundly affected his life and art"--